PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE TERHADAP HASIL BELAJAR RANAH KOGNITIF MATA PELAJARAN IPAS DI KELAS V SEKOLAH DASAR - Safitri, Desi; Sunarsih, Eti; Zulfahita, Zulfahita (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to examine the effect of the Picture and Picture cooperative learning model on the cognitive learning outcomes of fifth-grade students at SDN 21 Singkawang. A quantitative approach with a one-group pre-test-post-test pre-experimental design was employed. The sample included all fifth-grade students using saturated sampling. Data analysis consisted of normality testing, one-sample t-test, and effect size calculation to determine the impact of the learning model and its implementation. The results show a significant difference in students’ learning outcomes before and after using the Picture and Picture model, with t_calculated = 5.57765 ? t_table = 1.69389. The model also had a positive effect, as indicated by an increase in average scores from pretest = 31.88 to posttest = 91.25. Furthermore, the implementation of the model was rated as good to very good. These findings suggest that the Picture and Picture cooperative learning model is effective in improving cognitive learning outcomes for elementary school students and can be successfully applied in the classroom.